During the Pandemic Perceived Quality Forms Customer Loyalty via Brand Equity Oppo Smartphone Users - Ade Onny Siagian; Dodi Prasada; Agus Sudarsono; Hadion Wijoyo (UNEJ e-Proceeding, 2021)
This study aims to determine whether during the pandemic Perceived Quality has an effect on Customer Loyalty through Brand Equity on Oppo brand smartphone users in the Depok area. By using a quantitative research approach and SEM factor analysis methods as well as SPSS Amos 23 test equipment. The object of the analysis is consumers "Oppo brand smartphone users" in Depok. The research design used a single cross sectional, a sample of 150 respondents. The results showed that perceived quality had a significant effect on brand equity on Oppo smartphones in Depok with a regression coefficient of 0.882 and a critical ratio value of 6.891. Brand equity has a significant effect on customer loyalty on Oppo brand smartphones in Depok with a regression coefficient of 0.612 and a critical ratio value of 5.696. Perceived quality directly has no significant effect on customer loyalty on Oppo brand smartphones in Depok with a regression coefficient of 0.043 and a critical ratio value of 0.385. The indirect effect of perceived quality on customer loyalty > the direct effect of perceived quality on customer loyalty is 0.482 > 0.043, meaning that brand equity mediates between perceived quality and customer loyalty on Oppo Brand smartphones. Keywords: Pandemic, Perceived Quality, Brand Equity, Customer Loyalty